2021
DOI: 10.1002/onco.13885
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib and Evofosfamide (TH-302) in Systemic Treatment-Naïve Patients with Grade 1/2 Metastatic Pancreatic Neuroendocrine Tumors: The GETNE-1408 Trial

Abstract: Medical writing and statistical analyses were performed by Pau Doñate Ph.D. and Jordi Curto M.Sc., respectively, both from MFAR Clinical Research (Barcelona, Spain).GETNE-1408 trial was sponsored by Grupo Español de Tumores Neuroendocrinos y Endocrinos (GETNE). Threshold/MTEM provided evofosfamide and awarded a grant to GETNE to pay the costs of the study. Pfizer provided sunitinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…FDA has approved sunitinib for the treatment of renal cell carcinoma and gastrointestinal stromal tumors ( Ebos et al, 2007 ; Brooks et al, 2012 ). In addition, sunitinib also shows activity in clinical studies of neuroendocrine tumors, NSCLC, colon cancer, primary liver cancer, and breast cancer ( Ang et al, 2020 ; Li H et al, 2021 ; Chen et al, 2021 ; Grande et al, 2021 ; Symonds et al, 2021 ). What’s more, sunitinib also has been suggested as a radiosensitizing agent ( Curigliano et al, 2013 ; El Kaffas et al, 2013 ; Affolter et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…FDA has approved sunitinib for the treatment of renal cell carcinoma and gastrointestinal stromal tumors ( Ebos et al, 2007 ; Brooks et al, 2012 ). In addition, sunitinib also shows activity in clinical studies of neuroendocrine tumors, NSCLC, colon cancer, primary liver cancer, and breast cancer ( Ang et al, 2020 ; Li H et al, 2021 ; Chen et al, 2021 ; Grande et al, 2021 ; Symonds et al, 2021 ). What’s more, sunitinib also has been suggested as a radiosensitizing agent ( Curigliano et al, 2013 ; El Kaffas et al, 2013 ; Affolter et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brenner et al [43] reported a Phase II trial of bevacizumab and evofosfamide in bevacizumab-refractory glioblastoma, on the basis of induced hypoxia being an aspect of resistance to bevacizumab, but the response rate was very low (9%). Grande et al [44] carried out a recent Phase II clinical trial in pancreatic neuroendocrine tumours of Evofosfamide and the tyrosine kinase inhibitor sunitinib, suggesting that increased sunitinib-induced tumour hypoxia might promote activation of the prodrug, but the combination had high toxicity. Tran et al [45] used the kinase inhibitor sorafenib, but again with limited effectiveness.…”
Section: -Nitroimidazole Triggersmentioning
confidence: 99%
“…However, drug combinations still need to focus on the occurrence of adverse reactions. Sunitinib and evofosfamide had 88.2% systemic toxicity, failing in phase II clinical trials for G1/2 in metastatic pancreatic NETs [ 122 ]. During combined use, attention should be paid to the differences in pharmacokinetic properties and the in vivo distribution of different drugs, insufficient tumor accumulation, uncertain drug interactions in tumor tissues, and serious side effects.…”
Section: Tme-associated Combination Treatmentmentioning
confidence: 99%